Plasma Membrane-Type Aquaporins from Marine Diatoms Function as CO2/NH3 Channels and Provide Photoprotection. Issue 1 (3rd August 2018) - Matsui, Hiroaki; Hopkinson, Brian M.; Nakajima, Kensuke; Matsuda, Yusuke
Abstract : Diatom aquaporin-like channels mediate the permeability of cell membranes to CO2 and NH3 and help in mitigating high light stress. Abstract: Aquaporins (AQPs) are ubiquitous water channels that facilitate the transport of many small molecules and may play multiple vital roles in aquatic environments. In particular, mechanisms to maintain transmembrane fluxes of important small molecules have yet to be studied in marine photoautotrophic organisms. Here, we report the occurrence of multiple AQPs with differential cellular localizations in marine diatoms, an important group of oceanic primary producers. The AQPs play a role in mediating the permeability of membranes to CO2 and NH3 . In silico surveys revealed the presence of five AQP orthologs in the pennate diatom Phaeodactylum tricornutum and two in the centric diatom Thalassiosira pseudonana . GFP fusions of putative AQPs displayed clear localization to the plasma membrane (PtAGP1 and PtAQP2), the chloroplast endoplasmic reticulum (CER; PtAGP1 and PtAQP3), and the tonoplast (PtAQP5) in P. tricornutum . In T. pseudonana, GFP-AQP fusion proteins were found on the vacuole membrane (TpAQP1) and CER (TpAQP2). Transcript levels of both PtAQP1 and PtAQP2 were highly induced by ammonia, while only PtAQP2 was induced by high (1%[v/v]) CO2 . Constitutive overexpression of GFP-tagged PtAQP1 and PtAQP2 significantly increased CO2 and NH3 permeability in P. tricornutum, strongly indicating that these AQPs function in regulating CO2 /NH3 permeability in the plasma membrane and/or CER. Cells carrying GFP-tagged PtAQP1 and PtAQP2 had higher nonphotochemical quenching under high light relative to that of wild-type cells, suggesting that these AQPs are involved in photoprotection. These AQPs may facilitate the efflux of NH3, preventing the uncoupling effect of high intracellular ammonia concentrations.